Design and Analysis of MEMS Switch for RF Applications - K.Baranichandar, K.Balaji, (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper describes the design process of MEMSswitch and analysis of the MEMS switch structures for finding certain switch parameters to develop a highperformance RF MEMS switch with low voltage, low insertion loss and high isolation.The RF MEMS switchis designed using physical level approach by using 3DMEMS commercial software packages COMSOLMultiphysicsand Intellisuite. Theoptimization analysis is also simulated to obtain the low voltageby adjusting the air gap distance and top electrode designstructure. The RF performance is then simulated using theelectromagnetic analyzer, Emagto calculate the insertion loss andisolation value during the ON and OFF state conditions respectively. Severaldesigns are proposed and the best performance switch gives a lowvoltage actuation of 4V with low loss of8 dB and highisolation of -40 dB at 1.5GHz. The switch resistance of single switch is high. In order to reduce the effective switch resistance, 10 miniature RF MEMS switches have been placed in paralleland result in switchresistance of 5.9Ω